1986
DOI: 10.1111/j.1365-2591.1986.tb00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Paraesthesia—a consequence of a controversial root‐filling material? A case report

Abstract: Summary. This is a report of a case where a patient suffered paraesthesia following root filling of her lower left second molar. The Swedish health authorities considered that as a formaldehyde containing root filling cement had been used, the dentist had not worked in accordance with science and proven experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…However, the efficacy of long-term disinfec-tion by formaldehyde released from a root canal sealer appears to be low (Broisman et al 1978, Tronstad et al 1985. Moreover, there are case reports of adverse reactions such as paraesthesia of the inferior alveolar nerve attributed to the formaldehyde release from root canal sealers (Orlay 1966, Grossman 1978, Grossman & Tatoian 1978, Kaufman & Rosenberg 1980, érstavik et al 1983, Allard 1986, Erisen et al 1989, Gumru & Yalcin 1991. In addition, the systemic distribution of formaldehyde from different endodontic materials and medicaments has been shown in several studies (Myers et al 1978, Block et al 1980, Pashley et al 1980, Wemes et al 1982, Block et al 1983, Hata et al 1989, Araki et al 1993.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the efficacy of long-term disinfec-tion by formaldehyde released from a root canal sealer appears to be low (Broisman et al 1978, Tronstad et al 1985. Moreover, there are case reports of adverse reactions such as paraesthesia of the inferior alveolar nerve attributed to the formaldehyde release from root canal sealers (Orlay 1966, Grossman 1978, Grossman & Tatoian 1978, Kaufman & Rosenberg 1980, érstavik et al 1983, Allard 1986, Erisen et al 1989, Gumru & Yalcin 1991. In addition, the systemic distribution of formaldehyde from different endodontic materials and medicaments has been shown in several studies (Myers et al 1978, Block et al 1980, Pashley et al 1980, Wemes et al 1982, Block et al 1983, Hata et al 1989, Araki et al 1993.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, there are case reports of adverse reactions such as paraesthesia of the inferior alveolar nerve attributed to the formaldehyde release from root canal sealers ( Orlay 1966, Grossman 1978, Grossman & Tatoian 1978, Kaufman & Rosenberg 1980, Orstavik et al . 1983 , Allard 1986, Erisen et al . 1989 , Gumru & Yalcin 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, absorbability and toxicity are serious considerations with paraformaldehyde pastes. In a large number of reports published regarding paresthesia and other complications of the inferior alveolar nerve following penetration of root canal filling material into the mandibular canal, in most cases, damage to the nerve was specifically attributed to the highly irritating components of various paraformaldehyde pastes (93)(94)(95)(96)(97)(98)(99). Brodin (100) and other investigators (80,(101)(102)(103)(104)(105) have experimentally and convincingly demonstrated the neurotoxicity of these paraformaldehyde compounds.…”
Section: Paraformaldehydementioning
confidence: 99%
“…Thus, absorbability and toxicity are serious considerations with paraformaldehyde pastes. In a large number of reports published regarding paresthesia and other complications of the inferior alveolar nerve following penetration of root canal‐filling material into the mandibular canal, in most cases, damage to the nerve was specifically attributed to the highly irritating components of various paraformaldehyde pastes (47–53). Brodin (54) and other investigators (36, 55–59), have experimentally and convincingly demonstrated the neurotoxicity of these paraformadehyde compounds.…”
Section: Inflammatory and Neurotoxic Effects Of Root Canal Materialsmentioning
confidence: 99%
“…Reports in the literature involving serious injury to the inferior alveolar nerve have included paresthesia or anesthesia associated with overfill of N2 and similar paraformaldehyde pastes, (47, 48, 50, 52, 53), Endomethasone, (49, 62), AH26 (102–105), calcium hydroxide (99, 106), zinc‐oxide and eugenol, and gutta‐percha (72, 104). There is almost no current obturation material that has not been reported in the literature to produce paresthesia when overfilled into the neurovascular anatomy.…”
Section: Damage To the Neurovascular Anatomy: Causes And Outcomesmentioning
confidence: 99%